Investigation of Alumina Wetting by Fe-Ti, Fe-P and Fe-Ti-P Alloys - Karasangabo, Augustin; Bernhard, Christian (Journal of adhesion science and technology, 2012)
The wetting of alumina substrates by Fe-Ti, Fe-P and Fe-Ti-P alloys has been investigated using sessile drop experiments conducted under an inert gas atmosphere in the temperature range of 1550 to 1620°C. The surface and interfacial structures have been explored by scanning electron microscopy and energy dispersive X-ray spectroscopy. Substantial additions of titanium are known to induce steel melts to wet alumina due to the formation of a Ti-rich reaction product at the alloy/ceramic interface, but the present work has shown that even low Ti concentrations can induce a reactive wetting process leading to an improvement of the wettability of alumina by Fe alloys. The contact angle of molten steel containing phosphorus on alumina decreased with increasing P content. The improvement of the wetting behaviour in this system was attributed solely to the adsorption of P onto the surface of the Fe melt. The addition of P as a ternary alloying element to the system Fe-Ti proved to be beneficial to the wetting behaviour. The measured contact angles were much lower than those in the binary systems Fe-Ti and Fe-P. This effect was related to the fact that P enhances the activity of Ti in the Fe melt. According to experimental observations, it turns out that the wettability of liquid Fe-based alloys, when an Al2O3 surface is present, is not only a property of the metal/oxide couple but is also dependent on the oxygen partial pressure, whereas temperature variations bring about a comparatively small effect. This work is of interest in understanding the phenomena pertaining to inclusion engineering and steel- refractory interactions, such as the clogging of submerged entry nozzles by agglomerated alumina particles during the continuous casting process.